1990
DOI: 10.1007/bf01967830
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tissue concentrations of cefuroxime

Abstract: Cefuroxime is well-absorbed and distributed over the human body. This review gives a general summary of published information on tissue concentrations of cefuroxime after an intravenous or intramuscular dose of 750 or 1,500 mg of cefuroxime. Tissue concentrations are given for blister fluid, meninges, eyes, respiratory tract, sputum and bronchi, abdominal and urogenital tract, uterine, ovarian and fallopian tube tissue, myometrium, membranes, placenta, puruloid and healthy human milk, bile, prostate, hip and k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…With a deteriorating kidney function of 50 mL/min or less, cefuroxime is completely eliminated by glomerular filtration, 27 indicating that tubular secretion does not contribute to the renal elimination in case of renal impairment. To describe the decreasing function of the OAT-systems in renal impairment, the tubular excretion was implemented according to available literature values.…”
Section: Model Building-renally Impaired Adultsmentioning
confidence: 99%
“…With a deteriorating kidney function of 50 mL/min or less, cefuroxime is completely eliminated by glomerular filtration, 27 indicating that tubular secretion does not contribute to the renal elimination in case of renal impairment. To describe the decreasing function of the OAT-systems in renal impairment, the tubular excretion was implemented according to available literature values.…”
Section: Model Building-renally Impaired Adultsmentioning
confidence: 99%
“…The objective of an in vitro antimicrobial susceptibility test of the identified microorganism in the laboratory is to provide useful information to clinicians to predict the outcome of patients who receive antimicrobial treatment, usually empirical, and to allow adjustments when decreased susceptibility is identified. In the specific case of urinary tract infections, there is an important limitation in extrapolating this information because the concentration of various antibiotics used for treatment is usually considerably greater in kidney tissue and urine than in blood, as is the case for cefuroxime [ 15 ]. A small pharmacokinetic study from the 1980s showed that drug concentrations in urine were considerably greater than the minimum inhibitory concentration and were detected even after 12 h [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cefuroxime and flucloxacillin were analyzed by means of High Performance Liquid Chromatography (HPLC), as described before by van Dalen et al (l979), Hekster et al (1979Hekster et al ( , 1980, Roumen et al (1990). Vree and Hekster ( 1990).…”
Section: Methodsmentioning
confidence: 99%
“…The value of a high bone concentration of antibiotics is difficult to ascertain, although it is reasonable to assume that it is advantageous because the MIC value of the bacteria thus is exceeded (Levine and McCain 1978, Bryson et al 1979, Glover and Geddes 1981, Nelson et al 1982, Prober 1982, Gold and Rodriguez 1983, Vree and Hekster 1990, Wymenga et al 1991.…”
Section: Oral Versus Parenteral Administration In 20 Arthroplastiesmentioning
confidence: 99%